1994
DOI: 10.1136/jnnp.57.10.1166
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral responses to pain in patients with atypical facial pain measured by positron emission tomography.

Abstract: The localised PET cerebral correlates of the painful experience in the normal human brain have previously been demonstrated. This study examined whether these responses are different in patients with chronic atypical facial pain. The regional cerebral responses to nonpainfil and painful thermal stimuli in six female patients with atypical facial pain and six matched female controls were studied by taking serial measurements of regional blood flow by PET. Both groups displayed highly significant differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
121
2
8

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(142 citation statements)
references
References 38 publications
11
121
2
8
Order By: Relevance
“…These results are also consistent with other functional imaging studies that have suggested augmented central pain processing in chronic pain conditions, including fibromyalgia (27,55), irritable bowel syndrome (26), cerebral infarction complicated by allodynia (56), and atypical facial pain (57). In the only previous study that used functional neuroimaging to assess patients with low back pain, Derbyshire et al used positron emission tomography to compare cerebral responses to heat stimulation in patients with CLBP and healthy control subjects (58).…”
Section: Augmented Pain Processing In Idiopathic Chronic Low Back Painsupporting
confidence: 84%
“…These results are also consistent with other functional imaging studies that have suggested augmented central pain processing in chronic pain conditions, including fibromyalgia (27,55), irritable bowel syndrome (26), cerebral infarction complicated by allodynia (56), and atypical facial pain (57). In the only previous study that used functional neuroimaging to assess patients with low back pain, Derbyshire et al used positron emission tomography to compare cerebral responses to heat stimulation in patients with CLBP and healthy control subjects (58).…”
Section: Augmented Pain Processing In Idiopathic Chronic Low Back Painsupporting
confidence: 84%
“…In a study of older adults suffering from CLBP, Buckalew and colleagues [12] found a non-significant trend to decreased middle cingulate gyrus volumes in the patient group when compared with healthy controls. The results are supported by functional brain imaging studies that have revealed evidence for altered middle CC activity in different pain conditions [36][37][38] underlining the hypothesis that reduced MCC response is an adaptive cortical mechanism in acute pain that contributes to chronic pain development [12]. Nevertheless, we have to be careful interpreting these results with respect to chronic pain only.…”
Section: Discussionsupporting
confidence: 54%
“…It has been demonstrated to be either activated in experimental pain Derbyshire et al 1994), traumatic nociceptive pain (Hsieh et al 1996b) and chronic neuropathic pain . A prominent activation has also been demonstrated in unpleasant itch (Hsieh et al 1994), a situation with no pain but where the urge to scratch invokes body coordination.…”
Section: (H) Posterior Parietal Cortexmentioning
confidence: 99%